(Invited) Gravitational Level Effects on Electrochemical Interfacial Phenomena - Fukunaka, Yasuhiro (Meeting abstracts (Electrochemical Society), 2023)
Electrochemical copper refining technology invented in Niagara area made a great progress over more than 100 years through better understanding of natural convection phenomena. Ionic mass-transfer rate enhanced by natural convection developing along 1m high vertical electrode surfaces has been unconsciously utilized by trial-and-error method. As the local electrolyte composition is partly stratified in an electrolytic cell (roughly 5m long x 1.3m wide x 1.3m depth). The industrial electrolytic tank house is composed of about 1000 cells through which the electrolyte is continuously supplied. Thus, the electrolyte circulation is a key technology in industrial copper refining processes as well as appropriate selection of effective additive and stable sedimentation of anode slime containing precious metals on the electrolytic tank bottom. On the other hand, Cu nanowire arrays were electrodeposited potentiostatically with PC filter template in two kinds of electrolytic cell configurations: cathode over anode (C/A) and anode over cathode (A/C). The effect of gravitational level on the coupling phenomena between the morphological variation and the ionic mass transfer rate in nanosized pores(a mesoscopic scale of a fewμm high and 30nm in diameter) was also found. Hitherto, the coupling phenomena accompanied with the electrochemical interfacial reactions confined in such a mesoscopic space has not been studies in spite of the great technological interest for the production of micro- or meso-scale fabrication techniques encountered in microelectronics and energy conversion & storage technology field. The initial stage including nucleation and growth process during electrochemical phase transformation reactions must be at first focused to profoundly comprehend the present subject in order to reasonably design such an advanced device technology. Fundamental aspects in electrochemical processes in microgravity environments have not been frequently reported. However, Artemis projects may provide the large opportunities on the energy storage and power generation, as well as materials processing. The effects of gravitational level and magnetic field gradient on the electrochemical interfacial phenomena should be understood. The drop tower facility surely offers the appropriate & “unique” experimental opportunities to propose such research program in the future space engineering fields. Electrocrystallization of metals is selected as a good subject for starting direction of research. Its reaction mechanism is relatively simple, the deposition rate can be easily varied by changing the current density or potential, and a smooth copper film is deposited so long as it is not too thick. By the way, the damascene process has been introduced to copper wiring process in ULSI field by IBM almost 25 years ago. It is important to control the nucleation and crystal growth in the initial stages of electrodeposition process. For this purpose, many effects of additive have been intensively examined. However, few quantitative examinations have been reported on the coupling phenomena of ionic mass transfer and nucleation and crystal growth. In the present work, we introduce various gravitational levels as new parameters into the nonequilibrium electrochemical processing in order to create or tailor the unique physical properties in nano space field. It is fruitful in terms of physicochemical hydrodynamics that the experiments are done under various gravitational levels. In fact, it has been confirmed that the gravitational levels as well as the magnetic field introduce the intensified effects from that under 1 G normal environment. Here is a report to analyze the effect of gravitational level on the initial stages of Cu electrodeposition on TaN or TiN substrate.